Development of a wrist and hand stretching device for managing spasticity in stroke patients: a pilot study - Kim, Phillip Siwoo; Kim, Justin; Chen, Philbert; Chang, Min Cheol (Frontiers in Neurology, 2025)
ObjectivesWe developed a straightforward stretching device for the wrist and hand. To assess the device’s effectiveness in managing spasticity among chronic stroke patients.MethodsThe device, primarily constructed from plastic, comprises a forearm support module, a wrist module, and a finger module. Twenty stroke patients used the device four times daily, 7 days a week, for 1 month. Spasticity severity was measured using the Modified Ashworth Scale (MAS) for the wrist, thumb, and index fingers. A questionnaire evaluated the device’s feasibility and areas for improvement.ResultsBefore treatment, the mean MAS scores for the wrist, thumb, and index finger flexors were 1.50 ± 0.36, 1.52 ± 0.34, and 1.50 ± 0.30, respectively, compared with 1.25 ± 0.26, 1.27 ± 0.30, and 1.32 ± 0.33 post-intervention. Patients and occupational therapists expressed satisfaction with the device, citing its ease of use, effectiveness in stretching the wrist and fingers, and overall ease of manipulation. Half of the patients reported that all fingers were easily extended. The rigid plastic finger module was subsequently replaced with an inflatable, flexible rubber ball, providing a more comfortable contour for the stretched fingers, which increased user satisfaction.ConclusionThe stretching device effectively reduced spasticity in the wrist and hand, and the upgraded device enhanced patient satisfaction.